2021
DOI: 10.1042/bsr20203219
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin A inhibits A549 cell oxidative stress and apoptosis by modulating the PI3K/Akt/mTOR signaling pathway

Abstract: The excessive and inappropriate production of reactive oxygen species (ROS) can cause oxidative stress and is implicated in the pathogenesis of lung cancer. Cyclophilin A (CypA), a member of the immunophilin family, is secreted in response to ROS. To determine the role of CypA in oxidative stress injury, we investigated the role that CypA plays in human lung carcinoma (A549) cells. Here, we showed the protective effect of human recombinant CypA (hCypA) on hydrogen peroxide (H2O2)-induced oxidative damage in A5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…The production of ROS and MDA and the changes in SOD activity are important markers of oxidative stress in cells [ 12 ]. Previous studies have shown that ROS is an important mediator of H 2 O 2 -induced cell death [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…The production of ROS and MDA and the changes in SOD activity are important markers of oxidative stress in cells [ 12 ]. Previous studies have shown that ROS is an important mediator of H 2 O 2 -induced cell death [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, recent findings show that a significant pool of CyPA is an intra-mitochondrial factor, enhancing antiapoptotic signals, and hence suggesting a role in cell survival [20]. Indeed, CyPA was found to inhibit oxidative stress and apoptosis by modulating the PI3K/Akt/mTOR signaling pathway [21] in cancer cells. Here, we found that in response to Ivabradine, CyPA was accumulated in the necrotic area of pigs subjected to IR when compared to the placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the CypA/CD147 interaction inhibits the apoptosis of cancer cells [ 13 , 54 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ]. The antiapoptotic effects are associated with the upregulation of the PI3K/AKT/mTOR signaling pathway, modulation of the Bcl-2 family, and inhibition of caspase cascades [ 13 , 54 , 78 , 79 ]. Overexpression of CypA prevents hypoxia- and cisplatin-induced apoptosis in several cancer cell lines, including prostate cancer cells [ 56 ].…”
Section: Roles Of Cypa/cd147 Interaction In Cancermentioning
confidence: 99%